An Existence Result to a Strongly Coupled Degenerated System Arising in Tumor Modeling. (11th November 2008) - Hadjadj, L.; Hamdache, K.; Hamroun, D.
Abstract : We consider a mathematical model to describe the growth of a vascular tumor including tumor cells, macrophages, and blood vessels. The resulting system of equations is reduced to a strongly2 × 2 coupled nonlinear parabolic system of degenerate type. Assuming the initial data are far enough from 0, we prove existence of a global weak solution with finite entropy to the problem by using an approximation procedure and a time discrete scheme.